Waqf reporting in Malaysia / Rashidah Abd Rahman and Dalila Daud - Abd Rahman, Rashidah; Daud, Dalila (Research Management Institute (RMI), 2012)
This study is to investigate the reporting in Malaysian State Islamic Religious Councils using qualitative analysis. The lack of transparency is the supreme problem which derives from several attributes. There has been a little exploration on the prior studies focus more on other issues on waqf: administration, social, accounting etc. This study aiming to identify the current practice especially in reporting.